Evaluación al proceso contable de la cooperativa de ahorro y crédito “Fernando Daquilema” ltda., periodo 2017 - Shigla Gualli, Walter Reinaldo (2018)
The present investigation about the "COOPERATIVA DE AHORRO Y CRÉDITO FERNANDO DAQUILEMA” LTDA., ACCOUNTING ASSESSMENT PROCESS, PERIOD 2017" in the city of Riobamba parent agency, its main activity provide financial services, for the development of the community and the Puruha people. Its objective was to evaluate the accounting process of the cooperative and its relationship with the decisions taken during the year. Therefore, the following steps were elaborated: First: state of the art where we established the similar studies about the propose topic, the generalities of the Cooperativa de Ahorro y Crédito "Fernando Daquilema" Ltda., Mission, vision, objectives, legal basis , products and services, we continued with the second step: Theoretical framework, where the investigation was estableshed, the accounting process concepts, the accounting process origin, the accounting process importance, the accounting process, objective and the accounting process phases, as well as the decision making concepts, decision making process, accounting report and decision making and types of decision making, it helped to sustain, the approach to the problem. Third step: Research methodology, applied techniques in the investigation development, in this research project the deductive method and adequate and exposed information collection instruments were applied, finally the results and discussion which was presented according to the results obtained in the investigation.